(untitled) (Journal of Enam Medical College, 2018)
Background: Hepatitis caused by hepatitis E Virus (HEV) is not uncommon in developing countries. It is usually a self-limiting conferring immunity against subsequent infection. However, HEV infection during pregnancy results in varying degree of morbidity, often fatal. The present study was designed to find out the seroprevalence of subclinical HEV infection during pregnancy at different trimesters without history of hepatitis. Materials and Methods: A total 255 asymptomatic healthy pregnant women of three trimesters (85×3=255) with no history of jaundice were included in this cross-sectional study. The subjects were sub-grouped according to socioeconomic status and education level. HEV IgG antibody in serum was determined by enzyme linked immunosorbent assay (ELISA). Results were expressed as number (percent). Chi-square, Odds Ratio and 95% CI were calculated as applicable. Data analyses were carried out using statistical package for social science for Windows Version 15.0. A p<0.05 was taken as level of significance. Results: Seropositivity for HEV IgG was 38% (96/255) in pregnant women; the higher percentages were recorded in the 2nd and 3rd trimesters − 41% and 46% respectively. The seropositivity of HEV IgG was significantly high in pregnant women with low education level ((p=0.001; OR=2.70, 95% CI=1.602−4.575) and low socioeconomic status (OR=7.54, 95% CI=4.118−13.029) having monthly income below 27,000 taka (p=0.001). Conclusion: Data concluded that seroprevalence of anti-HEV IgG is higher at third trimester in pregnant women in Bangladesh where low socio-economic status and less education level were identified as possible risk factors. Appropriate measures may diminish the possible exposure to infection and reduce maternal mortality. J Enam Med Col 2018; 8(2): 85-89